Patients’ perception of quality of care in health facilities empanelled under Sehat-Card-Plus programme, in Khyber-Pakhtunkhwa, Pakistan - Kiran Sohail Azeemi; Shifa Salman Habib; Waqas Hameed; Junaid Ur Rehman Siddiqui; Ali Hussaini; Asma Altaf Hussain Merchant; Adil Haider; Sameen Siddiqi (Journal of the Pakistan Medical Association)
Objective:This study aims to assess perceived quality of care among users of hospitals empanelled under SCP Programme, KP. Methods: The assumed satisfaction level was 80% among SCP users, and 10%-point lower satisfaction among SCP nonusers. With a design effect of 1.5, 95% confidence level, and 80% power, the estimated total sample size was 972 patients, with equal group sizes of SCP users and SCP non-users. However, a total of 1,006 patients were included in the study, of which 517 were SCP users and 489 were non-SCP users. Total samples were distributed across 38 facilities in KP, proportional to average monthly admissions at each sampled facility. The data collection tool included 18 indicators of perceived quality of care, spread across 6 domains. Results:The overall satisfaction level with the quality of care among SCP users was found higher, 81%, relative to non-users, 79% (p<0.001). Disaggregated analysis across the study domains showed that the SCP non-users expressed higher perception about quality of hospital infrastructure and amenities relative to SCP users, whereas SCP users reported higher satisfaction with promptness of service, healthcare provider conduct, healthcare provider communication and quality of health service delivery. Only 326 (63%) users and 299 (61%) non-users were satisfied with healthcare provider communication. A total of 344 (67%) SCP users reported that Sehat Card Desk Representative gave them complete information about benefits and services under the programme. Conclusions: The SCP users reported high perceived quality of care. Further in-depth qualitative assessment is recommended to explain these findings. Keywords: Social health insurance, Quality of care, Sehat Card Plus Programme, Patient satisfaction, Khyber Pakhtunkhwa